OR04-02 The Role of the Sympathetic Nervous System in Metabolic Disorder and Adipose Dysfunction in Obesity and Aging - Sakamoto, Kenichi (J Endocr Soc, 2020)
Both obesity and aging increase susceptibility to metabolic disease and type 2 diabetes where adipose tissue dysfunction is a hallmark. In both conditions, impaired autonomic control is believed to play a key role in disrupted CNS control of metabolism. However, the role of the sympathetic nervous system (SNS) and catecholaminergic signaling in metabolic disease has not been well defined in large part due to a lack of suitable animal models(1). Surgical denervation is not specific to the SNS and chemical sympathectomy through 6-hydroxydopamine causes inflammation due to toxic effects. Abrogation of catecholamine (CA) synthesis in the whole body due to genetic deletion of the gene for tyrosine hydroxylase (th), a key enzyme in CA synthesis, results in embryonic lethality likely due to the lack of dopamine and norepinephrine in the CNS where they serve as key neurotransmitters. Here we studied the role of the SNS and catecholaminergic signaling in metabolic control in both aging as well as high fat diet (HFD) induced obesity. We created a mouse model of inducible th gene deletion that is restricted to the periphery, including sympathetic fibers of the peripheral NS but spares the brain as a pharmaco-genetic model of sympathectomy(2). TH is deleted and CA levels were reduced more than 90% in peripheral tissues of TH KO mice, while intact in the CNS. TH KO mice are cold intolerant consistent with functional sympathectomy. Interestingly, TH KO mice are protected from HFD feeding induced glucose intolerance (AUC during GTT: WT1018.8±42.0 mg/dl/hr vs. TH KO 485.0±85.8 mg/dl/hr; p < 0.0001; n = 6) even though food intake increased in TH KO mice. In 20 months old TH KO mice glucose tolerance was improved and fasting blood glucose levels were reduced (AUC during GTT: WT 357.3±16.2 mg/dl/hr vs. TH KO 254.5±15.6 mg/dl/hr; p < 0.01; n = 12) with higher insulin levels (WT 0.35±0.07 μg/l vs. TH KO 1.28±0.28 μg/l; p < 0.001; n = 9). Of note, insulin tolerance tests did not show marked differences. Both obesity and aging are characterized by impaired adipose tissue function with reduced lipogenic capacity. TH KO mice fed a HFD exhibit increased WAT de novo lipogenesis, lower lipolysis, and trend to exhibit decreased adipose tissue inflammation, suggesting that the SNS is a major culprit for the impaired lipogenic capacity in adipose tissue. Our data provides support for the paradigm that impaired SNS function plays an important role in the dysmetabolic states of obesity and aging. Reference 1. Ryu V, Buettner C. Fat cells gobbling up norepinephrine? PLoS Biol. 2019;17(2):e3000138. 2. Fischer K, Ruiz HH, Jhun K, Finan B, Oberlin DJ, van der Heide V, et al. Alternatively activated macrophages do not synthesize catecholamines or contribute to adipose tissue adaptive thermogenesis. Nature medicine. 2017;23(5):623-30.